Polish Catholic Bishops, Nationalism and Liberal Democracy - Meyer Resende, Madalena (Religions, 2021)
The alliance of the Polish Catholic Church with the Law and Justice (PiS) government has been widely reported and resulted in significant benefits for the Church. However, beginning in mid-2016, the top church leadership, including the Episcopal Conference, has distanced itself from the government and condemned its use of National Catholicism as legitimation rhetoric for the government’s malpractices in the fields of human rights and democracy. How to account for this behavior? The article proposes two explanations. The first is that the alliance of the PiS with the nationalist wing of the Church, while legitimating its illiberal refugee policy and attacks on democratic institutions of the government, further radicalized the National Catholic faction of the Polish Church and motivated a reaction of the liberal and mainstream conservative prelates. The leaders of the Episcopate, facing an empowered and radical National Catholic faction, pushed back with a doctrinal clarification of Catholic orthodoxy. The second explanatory path considers the transnational influence of Catholicism, in particular of Pope Francis’ intervention in favor of refugee rights as prompting the mainstream bishops to reestablish the Catholic orthodoxy. The article starts by tracing the opposition of the Bishops Conference and liberal prelates to the government’s refugee and autocratizing policies. Second, it describes the dynamics of the Church’s internal polarization during the PiS government. Third, it traces and contextualizes the intervention of Pope Francis during the asylum political crisis (2015-2016). Fourth, it portrays their respective impact: while the Pope’s intervention triggered the bishops’ response, the deepening rifts between liberal and nationalist factions of Polish Catholicism are the ground cause for the reaction.